DEVELOPMENT OF A GAMIFICATION-BASED READING LEARNING PROGRAM FOR CHILDREN WITH DYSLEXIA - Rahmanissa, Fashihah; Susetyo, Budi; Rochyadi, Endang; Tarsidi, Iding; Tambrin, Nita Nitya Intan; Kusumastuti, Shinta Dewi; Hapsari, Elvina (JPI (Jurnal Pendidikan Inklusi), 2025)
This study aims to develop a gamification-based reading learning program as a form of innovation in supporting the literacy skills of children with dyslexia. The background of this study is the limited adaptive and enjoyable learning media for children with specific barriers in reading, as well as the need for interventions that can facilitate phonological awareness and word recognition effectively. This study uses a descriptive approach with a simplified research and development (R&D) method in three stages, namely Needs Analysis, program Development, and validation by experts. Data were obtained through initial assessment, interviews with teachers and parents, and validation through focus group discussions. The results showed that programs designed according to the characteristics of children with dyslexia, utilize gamification elements such as points, levels, visual feedback, and interactive narratives. Expert validation shows that the program is feasible to use and can be an attractive and responsive alternative learning medium. Although this study does not yet include direct implementation trials, the development results make an initial contribution in designing a more personalized and enjoyable learning approach for children with special needs in reading.